2020
DOI: 10.1097/hjh.0000000000002755
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequency and pattern of night shift on hypertension risk in female nurses: a cross-sectional study

Abstract: Objectives: Understanding the effect of night shift on hypertension risk in nurses is important to improve the health of nurses and ensure patient safety. This study aimed to evaluate the effect of the frequency and pattern of night shift on hypertension risk and the interaction of them in female nurses.Methods: This cross-sectional study constituted 84 697 female nurses in 13 cities in China. The main contents of the survey included SBP, DBP, the frequency and pattern of night shift, and some other factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(25 reference statements)
1
8
1
Order By: Relevance
“…We enjoyed reading the article titled ‘Effect of frequency and pattern of night-shift on hypertension risk in female nurses: a cross sectional study’ [1]. This investigation found that there was a positive association between nurses’ frequency and pattern of night shifts and hypertension, even after accounting for several confounders, including BMI, marital status, physical activity and preexisting conditions such as history of hyperlipidaemia and diabetes.…”
mentioning
confidence: 99%
“…We enjoyed reading the article titled ‘Effect of frequency and pattern of night-shift on hypertension risk in female nurses: a cross sectional study’ [1]. This investigation found that there was a positive association between nurses’ frequency and pattern of night shifts and hypertension, even after accounting for several confounders, including BMI, marital status, physical activity and preexisting conditions such as history of hyperlipidaemia and diabetes.…”
mentioning
confidence: 99%
“…A meta‐analysis of five cohort studies showed that a 5‐year increase in shift work was associated with a 5% increased risk of CVD (Wang et al., 2018 ). A cohort study among nurses found that those with 10 or more night shifts per month were significantly more likely to have high blood pressure (Zhao et al., 2021 ), the potential mechanism might be that shift work leads to circadian disruption, systemic inflammation, and decreased melatonin production (Folkard, 2008 ). It is generally known that the different job is affected by the education level.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in six men suggested that elevated BP due to staying awake for one night may stem from baroreflex resetting toward higher BP levels [ 20 ]. In addition, the well-known suppression of the pineal gland hormone melatonin due to night work [ 21 ] may represent another potential mechanism underlying the association between night shift work and hypertension [ 1 , 2 , 3 ]. As suggested by both animal and human studies, melatonin, which is mainly released in the absence of environmental light, demonstrates significant hypotensive effects that can extend into the following day [ 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent meta-analysis based on 45 studies involving 117,252 workers found that permanent night workers had a ~2.5 mmHg higher systolic BP and ~2 mmHg higher diastolic BP compared to daytime workers [ 1 ]. Furthermore, in a cross-sectional study from China involving over 80,000 female nurses, working at least five nights per month increased hypertension risk by 19% to 32% [ 2 ]. Finally, a recent study based on data from the UK Biobank demonstrated that night shift workers had a higher hypertension risk than day shift workers, which increased with the increasing frequency of night shift work [ 3 ].…”
Section: Introductionmentioning
confidence: 99%